You can take x = a, 2y = b and then can apply the binomial theorem.
The expansion of given expression is given by:
Option D:
is
<h3>What is binomial theorem?</h3>
It provides algebraic expansion of exponentiated(integer) binomial.
According to binomial theorem,
![(a+b)^n = \sum_{i=0}^n ^nC_i a^ib^{n-i}](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%3D%20%5Csum_%7Bi%3D0%7D%5En%20%5EnC_i%20a%5Eib%5E%7Bn-i%7D)
<h3>How to use binomial theorem for given expression?</h3>
Taking a = x, and b =2y, we have n = 7, thus:
![(x+2y)^7 = \: ^7C_0x^0(2y)^7 + \: ^7C_1x^1(2y)^6 + \: ^7C_2x^2(2y)^5 + \: ^7C_3x^3(2y)^4 + \:^7C_4x^4(2y)^3 + \:^7C_5x^5(2y)^2 + \:^7C_6x^6y^1 + \: ^7C_0x^7y^0\\\\ (x+2y)^7 = 128y^7 + 448xy^6 + 672x^2y^5 + 560x^3y^4 + 280x^4y^3 + 84x^5y^2 + 14x^6y + x^7\\\\ (x+2y)^7 = x^7 + 14x^6y + 84x^5y^2 + 280x^4y^3 + 560x^3y^4 + 672x^2y^5 + 448xy^6 + 128y^7](https://tex.z-dn.net/?f=%28x%2B2y%29%5E7%20%3D%20%5C%3A%20%5E7C_0x%5E0%282y%29%5E7%20%2B%20%5C%3A%20%5E7C_1x%5E1%282y%29%5E6%20%2B%20%5C%3A%20%5E7C_2x%5E2%282y%29%5E5%20%2B%20%5C%3A%20%5E7C_3x%5E3%282y%29%5E4%20%2B%20%5C%3A%5E7C_4x%5E4%282y%29%5E3%20%2B%20%5C%3A%5E7C_5x%5E5%282y%29%5E2%20%2B%20%5C%3A%5E7C_6x%5E6y%5E1%20%2B%20%5C%3A%20%5E7C_0x%5E7y%5E0%5C%5C%5C%5C%0A%28x%2B2y%29%5E7%20%3D%20128y%5E7%20%2B%20448xy%5E6%20%2B%20672x%5E2y%5E5%20%2B%20560x%5E3y%5E4%20%2B%20280x%5E4y%5E3%20%2B%2084x%5E5y%5E2%20%2B%2014x%5E6y%20%2B%20x%5E7%5C%5C%5C%5C%0A%28x%2B2y%29%5E7%20%3D%20x%5E7%20%2B%2014x%5E6y%20%2B%2084x%5E5y%5E2%20%2B%20280x%5E4y%5E3%20%2B%20560x%5E3y%5E4%20%2B%20672x%5E2y%5E5%20%2B%20448xy%5E6%20%2B%20128y%5E7)
Thus, Option D:
is correct.
Learn more about binomial theorem here:
brainly.com/question/86555